Description and bioacoustics of a new species of the genus Isophya (Orthoptera: Tetigoniidae: Phaneropterinae) from Turkey - Sevgi̇li̇, Hasan; Demi̇rsoy, Ali̇; Çiplak, Battal (Zootaxa, 2012)
A new species for the genus Isophya, I. bumerangoides, is described from the Northeastern Black Sea Region of Turkey. Thenew species differs from closely related species in some aspects of morphology, mainly in male and female genitalia. Illustra-tions of external morphological characters and male and female songs are provided. Additional data on male calling song andfemale song of closely related bush-cricket Isophya rizeensis Sevgili, 2003 are also given. Scanning Electron Microscopeimages of stridulatory file of the other related species I. redtenbacheri Adelung, 1907 are provided. I. bumerangoides clearlybelongs to I. amplipennis group. Our bioacoustic results suggest that within the genus Isophya, changes in calling song seem to appear more slowly than those in external morphological characters as in most tettigoniid.